Colin Stanton’s Copycat Crime in Jeffery Deaver’s The Bone Collector - dewi puspita sari wibowo (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Crime is known as an act which conducted by criminal(s). Copycat crime is one of the methods which commonly be used among criminal(s). Easiest to be followed, modified also adapted are the reasons why this method famed among the media. In Jeffery Deaver’s The Bone Collector, the author used the copycat crime method as a method that is used by the antagonist character named Colin Stanton. Colin Stanton copied a character named James Schneider from the book titled Crime in Old New York. The reasons of Colin Stanton copying a character together with the implications of the decision Colin Stanton has made as a murderer are two statements which is answered using Theory of imitation proposed by Gabriel Tarde together with trans-theoretical model of change behavior that proposed by Robert D. Hare. These two theory resulted Colin Stanton lacked of knowledge on himself and with his action, James Schneider used as a spiritual guide for him. It is also proven the implication of Colin Stanton behavior being a murderer was change. Colin Stanton behavior change from a lovable man into a psychopath. Keywords: Crime, copycat crime, laws of imitation, trans-theoretical model of change behavior, psycopath